Effects of caspofungin, Candida albicans and Aspergillus fumigatus on toll-like receptor 9 of GM-CSF-stimulated PMNs - Salvenmoser, Stefanie; Seidler, Marc; Dalpke, Alexander; Müller, Frank-Michael (FEMS immunology and medical microbiology, 2010)
The possible involvement of Toll-like receptors (TLRs) 1, 2, 4 and 9 in the interaction of antifungal drugs with polymorphonuclear neutrophils (PMNs) in response to Aspergillus fumigatus and Candida albicans as stimuli was investigated. Caspofungin revealed the broadest capacity to enable C. albicans and A. fumigatus to stimulate TLR upregulation, TLR 2 by A. fumigatus and TLRs 4, 9 by C. albicans. Conventional amphotericin B (cAMB) stimulated only A. fumigatus to induce TLRs 2 and 4 upregulation; voriconazole stimulated A. fumigatus and fluconazole C. albicans to induce TLR 9 upregulation. For cAMB, only TLR 9 was upregulated by A. fumigatus, whereas in the case of voriconazole, TLRs 2, 4, 9 were upregulated. Caspofungin revealed the broadest capacity: C. albicans was stimulated to upregulate TLRs at least at one of the concentrations, and A. fumigatus was stimulated to upregulate TLRs 2, 4. TLR 9 was upregulated two to three fold by all antifungal drugs on protein, except for fluconazole at the RNA level. Candida albicans preincubated with caspofungin has additional effects on CD11b expression and IL8 chemotaxis in CpG-DNA-stimulated PMNs. These results indicate a relevant upregulation with a functional relevance of TLR 9 in the presence of C. albicans strains preincubated with caspofungin at three concentrations.
Gesehen am 30.06.2023